The Interplay Between Chamber Musicians During Two Public Performances of the Same Piece: A Novel Methodology Using the Concept of “Flow” - Horwitz, Eva Bojner; Harmat, László; Osika, Walter; Theorell, Töres (Frontiers in Psychology, 2021)
The purpose of the study is to explore a new research methodology that will improve our understanding of "flow" through indicators of physiological and qualitative state. We examine indicators of ‘flow’ experienced by musicians of a youth string quartet, two women (25, 29), and two men (23, 24). Electrocardiogram (ECG) equipment was used to record heart rate variability (HRV) data throughout the four movements in one and the same quartet performed during two concerts. Individual physiological indicators of flow were supplemented by assessments of group ‘state flow’ (means from standardized questionnaires) and a group interview in which the musicians provided qualitative data. A matrix was constructed for the characterization of different kinds of demands in the written music in each one of the four movements for each one of the musicians. HRV derived from ECG data showed non-significant trends for group state flow across the eight musical episodes. Individual-level analysis showed that compared to the other players the first violin player had the highest mean heart rate and the lowest increase in High Frequency power (HF) in HRV during this particular movement, particularly during the second concert. The qualitative data illustrated how an interplay of synchronised social interactions between this player and their colleagues during the musical performance was associated with a feeling of group state flow and served to support the first violinist. The case illustrates that the proposed mixed methodology drawing on physiological and qualitative data, has the potential to provide meaningful information about experiences of a flow state, both at individual and group level. Applications in future research are possible.